Oncogenic Actions of the Nuclear Receptor Corepressor (NCOR1) in a Mouse Model of Thyroid Cancer - Fozzatti, Laura (Public Library of Science, 2013)
Studies have suggested that the nuclear receptor corepressor 1 (NCOR1) could play an important role in human cancers. However, the detailed molecular mechanisms by which it functions in vivo to affect cancer progression are not clear. The present study elucidated the in vivo actions of NCOR1 in carcinogenesis using a mouse model (Thrb(PV/PV) mice) that spontaneously develops thyroid cancer. Thrb(PV/PV) mice harbor a dominantly negative thyroid hormone receptor β (TRβ) mutant (denoted as PV). We adopted the loss-of-the function approach by crossing Thrb(PV) mice with mice that globally express an NCOR1 mutant protein (NCOR1ΔID) in which the receptor interaction domains have been modified so that it cannot interact with the TRβ, or PV, in mice. Remarkably, expression of NCOR1ΔID protein reduced thyroid tumor growth, markedly delayed tumor progression, and prolonged survival of Thrb(PV/PV)Ncor1 (ΔID/ΔID) mice. Tumor cell proliferation was inhibited by increased expression of cyclin-dependent kinase inhibitor 1 (p21(waf1/cip1); Cdkn1A), and apoptosis was activated by elevated expression of pro-apoptotic BCL-Associated X (Bax). Further analyses showed that p53 was recruited to the p53-binding site on the proximal promoter of the Cdkn1A and the Bax gene as a co-repressor complex with PV/NCOR1/histone deacetylas-3 (HDAC-3), leading to repression of the Cdkn1A as well as the Bax gene in thyroids of Thrb(PV/PV) mice. In thyroids of Thrb(PV/PV)Ncor1 (ΔID/ΔID) mice, the p53/PV complex could not recruit NCOR1ΔID and HDAC-3, leading to de-repression of both genes to inhibit cancer progression. The present studies provided direct evidence in vivo that NCOR1 could function as an oncogene via transcription regulation in a mouse model of thyroid cancer.